Uncovering the neuroprotective effect of vitamin B12 in pneumococcal meningitis: insights into its pleiotropic mode of action at the transcriptional level - Cassiano, Larissa Marcely Gomes; Oliveira, Marina da Silva; de Queiroz, Karina Barbosa; Amancio, Alice Muglia Thomaz da Silva; Salim, Anna Christina de Matos; Fernandes, Gabriel da Rocha; Carneiro, Cláudia Martins; Coimbra, Roney Santos (Frontiers in Immunology, 2023)
The interplay between bacterial virulence factors and the host innate immune response in pneumococcal meningitis (PM) can result in uncontrolled neuroinflammation, which is known to induce apoptotic death of progenitor cells and post-mitotic neurons in the hippocampal dentate gyrus, resulting in cognitive impairment. Vitamin B12 attenuates hippocampal damage and reduces the expression of some key inflammatory genes in PM, by acting as an epidrug that promotes DNA methylation, with increased production of S-adenosyl-methionine, the universal donor of methyl. Material and Methods: Eleven-day-old rats were infected with S. pneumoniae via intracisternal injection and then administered either vitamin B12 or a placebo. After 24 hours of infection, the animals were euthanized, and apoptosis in the hippocampal dentate gyrus, microglia activation, and Código de campo alterado Formatado: Fonte: Itálico Formatado: Fonte: Itálico the inflammatory infiltrate were quantified in one brain hemisphere. The other hemisphere was used for RNA-Seq and RT-qPCR analysis. Results: In this study, adjuvant therapy with B12 was found to modulate the hippocampal transcriptional signature induced by PM in infant rats, mitigating the effects of the disease in canonical pathways related to the recognition of pathogens by immune cells, signaling via NF-kB, production of pro-inflammatory cytokines, migration of peripheral leukocytes into the central nervous system, and production of reactive species. Phenotypic analysis revealed that B12 effectively inhibited microglia activation in the hippocampus and reduced the inflammatory infiltrate in the central nervous system of the infected animals. These pleiotropic transcriptional effects of B12 that lead to neuroprotection are partly regulated by alterations in histone methylation markings. No adverse effects of B12 were predicted or observed, reinforcing the well-established safety profile of this epidrug.Conclusion: B12 effectively mitigates the impact of PM on pivotal neuroinflammatory pathways. This leads to reduced microglia activation and inflammatory infiltrate within the central nervous system, resulting in the attenuation of hippocampal damage. The anti-inflammatory and neuroprotective effects of B12 involve the modulation of histone markings in hippocampal neural cells.